Impending tyroid storm - Pretika Prameswari; Mohamad Fadli (Institute of Computer Science (IOCS), 2022)
Thyroid storm is an emergency and requires immediate treatment. Diagnosing thyroid storm is difficult because of its clinical symptoms that mimic infection such as tachycardia, high fever, and sometimes shortness of breath. This study employs a case study approach. The research subjects were patients with impending thyroid storm. The research location is in the Emergency Unit of Cibinong Hospital. Data analysis techniques using literature studies. In this case, a 30-year-old man at the Emergency Unit of Cibinong Hospital presented a clinical Impending Thyroid Storm with multi-organ involvement including Thyroid Heart Disease in the form of Atrial Fibrillation, gastrointestinal complaints, Hypoglycemia accompanied by Respiratory Failure. The patient has been diagnosed with Graves Disease for 5 years. Treatment for this patient includes correction of hypoglycemia, diuretics and digoxin. Propylthiouracil (PTU) and Propranolol were given when the FT4 and TSH results were out. After being treated with this therapy, clinically improved, marked by reduced tightness, fever and palpitations. On the ecg examination, atrial fibrillation was not found again. Recognizing Thyroid Storm as early as possible can prevent the severity of complications. Hypoglycemia correction is no less important. PTU therapy, Propranolol, Furosemide, Spironolactone and Digoxin are still good therapeutic modalities to be used, especially in type B hospitals.